Formulation of Criminal Law Policy Against Influence Trading as A Criminal Act of Corruption - Chandra Matdung; Fauzie Yususf Hasibuan; Lilik Mulyadi (Jurnal Indonesia Sosial Sains, 2024)
The act of trading in influence is still not considered as a criminal offence so that until now the regulations governing it do not exist or have not been regulated in Indonesia. This research aims to examine the regulation of the formulation of trading in influence as a Corruption Crime according to positive law and analyse the criminal law policy towards the formulation of trading in influence as a Corruption Crime in the future. The research method used is normative juridical with analytical approach, with the specification of description analysis. The results showed that the absence of regulation regarding the formulation of the offence of trading in influence in Indonesian positive law causes law enforcement officials to often use the offence of bribery to criminalise while between bribery and trading in influence are two different things. The offence is different from the offence of bribery and other corruption offences so it is necessary or a different crime from the category of corruption-related crimes covered by the relevant Legislation. In order to achieve the objectives of the law as stated in Article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia that Indonesia is a State of law, as a form of legal development through legal policies that formulate existing rules with elements, namely each party involved, the form of trading in influence regulated in the respective regulations, the perpetrators who carry out these acts, the form of action and also the form of giving and receiving from the parties for one purpose, namely obtaining an undue advantage or benefit. Specifically, the article on trading in influence in Law Number 31 of 1999 jo Law Number 20 of 2001 concerning Eradication of Corruption so that there is no legal vacuum in the event of a case related to trading in influence